My “Close Encounters” in World War 2 Combat - Thayer Greene (Close Encounters in War Journal, 2020)
As a 19 year old young man, Thayer Greene had his “close encounter” with the great world conflict at the end of winter of 1945, as he was deployed as an infantryman to Europe and took part in the battle for Cologne. In this article, the author recollects a few of his relevant close encounters with war and with the emotions that characterised those moments, from fear to hilariousness, up to sheer terror that eventually haunted him for decades as PTSD. This long suppressed spiritual suffering urged him to train in Jungian psychotherapy in the 1960s and finally to deal with his traumatic memories in the late 1970s. This text tells the story of that journey from trauma to healing.